2018
DOI: 10.2106/jbjs.16.01379
|View full text |Cite
|
Sign up to set email alerts
|

Creep and Wear in Vitamin E-Infused Highly Cross-Linked Polyethylene Cups for Total Hip Arthroplasty

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…Other Level-I and II studies demonstrated significantly less wear for vitamin E-infused HXLPE compared with UHMWPE 20 , medium cross-linked polyethylene 21 , and HXLPE without vitamin E 22 at mid-term follow-up.…”
Section: Highly Cross-linked Polyethylene (Hxlpe)mentioning
confidence: 87%
“…Other Level-I and II studies demonstrated significantly less wear for vitamin E-infused HXLPE compared with UHMWPE 20 , medium cross-linked polyethylene 21 , and HXLPE without vitamin E 22 at mid-term follow-up.…”
Section: Highly Cross-linked Polyethylene (Hxlpe)mentioning
confidence: 87%
“…Wyss et al [6] found 0.09 mm per y and Lafon et al [7] found 0.07 mm per y. Rochcongar et al recently performed a prospective randomized controlled study comparing RM Pressfit cup (UHMWPE) to RM Pressfit vitamys cup (HXLPE/VitE) and confirmed that wear rates over the first three years following surgery were lower for the HXLPE blended with vitamin-E [2]. This might directly affect the need of late revision surgery.…”
Section: Discussionmentioning
confidence: 97%
“…The most challenging requirement in THA is a long implant survival. Aseptic loosening of the components is one of the most prevalent causes for revision surgery [2,3]. In the last decades, a substantial effort has been made to avoid or prolong aseptic loosening and mechanical failure of the implants, and this will remain a major challenge in the future [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While wear produces particles of debris, creep does not 5 . More recently, it is thought that the initial “loss” period may be even shorter and estimated to be 3 to 6 months 6 , 7 .…”
Section: Creepmentioning
confidence: 99%